Determination of Soil Properties by Using Multi-Channel Analysis Method Records of Microtremor, Earthquake and Surface Waves: A Sample Implementation from AFAD Campus - Erkan Ateş (Doğal Afetler ve Çevre Dergisi)
The most valid way to determine the soil amplification is to use the analysis of strong ground motion records. The Earthquake Observation Station located in Ankara AFAD campus was established in 2014. There are many official institutions such as Ankara Bilkent City Hospital, Ministry of Health, Ministry of Agriculture and Forestry, and Ministry of Trade within the working area. Since the earthquake station was established, 22 earthquake records have been registered. Multichannel analysis of surface waves (MASW) was measured to calculate the average shear wave velocity of the upper 30 and 50 meters of the soil where the station was located. 14 earthquake records of different magnitudes and distances occurring in different fault zones recorded by the station were interpreted using the horizontal / vertical ratio technique according to the single station method, and the amplification factor and dominant vibration frequency of the soil were calculated. Apart from the earthquake records, 4 hours of microtremor measurements were made with the CMG-6TD broadband seismometer, and the measurements were evaluated according to the single station method and the horizontal / vertical spectral ratio technique. The results of MASW, microtremor and earthquake records were compared, and the dynamic properties of soil were studied. According to the results obtained from the analysis of earthquake and microtremor records, it has been observed that the amplification factor and predominant frequencies are very close to each other, compatible to the soil class calculated by using the shear wave velocity.